Planned obsolescence: publishing, technology and the future of the academy, de Kathleen Fitzpatrick - Vecchio, Pollyanna de Mattos Moura (Texto Livre, 2013)
Resenha por Pollyanna de Mattos Moura Vecchio/CEFET-MG.